Thunder Over Lolo Pass - West, Charles (Penguin Group USA, 2011)
Roberta Morris goes to the McCloud brothers seeking help in finding her uncle. He's gone missing in the Bitterroot Mountains while mining for gold. They are happy to oblige a pretty little lady who's all alone. But she's not alone. Frank Burdette and his gang are hot on her trail, and they know more than Roberta is letting on to the McClouds.